2017
DOI: 10.1590/1806-9282.63.01.29
|View full text |Cite
|
Sign up to set email alerts
|

Experimental burns: Comparison between silver sulfadiazine and photobiomodulation

Abstract: Objective: To analyze morphological characteristics and organization of the collagen fibers of third degree burns from scalding compared to laser therapy and silver sulfadiazine, the latter considered as the gold standard. Method: Were selected 12 animals (Rattus norvegicus) also divided into three groups (control group [CG] -untreated burns; sulfadiazine group [SG] -burns were treated with silver sulfadiazine at 1%; laser group [LG] -burns were treated with photobiomodulation). The scald burns were carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Of these, 1164 were excluded for not meeting the inclusion criteria of this systematic review: repeated study (n = 5), in vitro study (n = 120), clinical study (n = 62), systematic review (n = 76), ab-stract only (n = 47), it is not of third-degree burn (n = 854). Finally, 17 studies [4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] in which diverse treatment pa-rameters of injuries were assessed were included for critical evaluation of the effectiveness of PBMT in third-degree burn. The 17 selected studies totaled a sample of 845 animals and showed some common characteristics, namely the use of adult male Wistar rat with a mean weight of 278.5 g as an experimental model and the dorsal region of the animals as the region where burns were performed in all (100%) studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 1164 were excluded for not meeting the inclusion criteria of this systematic review: repeated study (n = 5), in vitro study (n = 120), clinical study (n = 62), systematic review (n = 76), ab-stract only (n = 47), it is not of third-degree burn (n = 854). Finally, 17 studies [4,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] in which diverse treatment pa-rameters of injuries were assessed were included for critical evaluation of the effectiveness of PBMT in third-degree burn. The 17 selected studies totaled a sample of 845 animals and showed some common characteristics, namely the use of adult male Wistar rat with a mean weight of 278.5 g as an experimental model and the dorsal region of the animals as the region where burns were performed in all (100%) studies.…”
Section: Resultsmentioning
confidence: 99%
“…Burns are the most extensive forms of soft tissue injuries, occasionally resulting in extensive and deep wounds and death. Burns can lead to severe mental and emotional distress, because of excessive scarring and skin contractures [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagen deposition observed in this study was related to type III collagen. In fact, we analyzed the samples on the 14-2021876820 th day after the operative procedure, at which time the collagen type I deposition was not yet observed [37]. Furthermore, a better organization of the collagen fibers implies a better cicatricial process [38].…”
Section: Discussionmentioning
confidence: 99%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%